In Silico Drug Discovery Identifies Stigmasterol from Red Betel (Piper crocatum Ruiz & Pav) Stem as a Potential Antidiabetic Agent - Sari, Putri Kharisma Novita; Febyaningrum, Vitasigi Dwi (Journal of Tropical Life Science, 2026)
Type 2 diabetes (T2DM) is a metabolic disorder caused by insufficient insulin secretion and the inability of tissues to respond to insulin. Therapy can include the use of insulin in conjunction with other glucose-lowering agents, but these drugs have several limitations related to efficacy, tolerability, and potential side effects. The use of herbal medicines has begun to develop as a therapeutic option, including stigmasterol. Stigmasterol, which has been successfully isolated from several plants, has demonstrated antidiabetic activity in both in vivo and in vitro studies. This study aimed to conduct a comprehensive exploration of the potential, mechanism of action, protein targets, and profile of stigmasterol found in red betel stem as a candidate natural antidiabetic agent in silico. The results of this study indicate that stigmasterol has potential as a drug candidate for the therapy of T2DM with a predicted limited level of toxicity. Computational analyses suggest that stigmasterol may possess therapeutic potential against T2DM by regulating biological processes associated with insulin resistance and the AMPK signaling pathway, potentially through interactions with the key targets STAT3, AKT1, NFKB1, HMGCR, MTOR, and ACACA. Both ligand-based (Support Vector Machine regression) and structure-based (molecular docking) approaches show promising results regarding the activity of this compound. Therefore, stigmasterol is predicted as a potential candidate for further development as a natural antidiabetic agent through the multitarget mechanism of action generated from this modeling. However, the pharmacokinetic profile of stigmasterol indicates potential challenges in meeting drug-likeness criteria, which require further experimental validation.